Damage detection in bonded repairs using piezoceramics - Chiu, W K; Galea, S C; Koss, L L; Rajic, N (Smart materials and structures, 2000)
This paper reports on the development of a perceptive repair or smart system which will provide information on the in-service performance of the repair and the associated aerospace structure. In this respect, this paper focuses on the detection of disbond in the adhesive layer between adhered (boron/epoxy unidirectional composite) and the metallic parent (Al) structure. One of the criteria of this smart system is that it must be economical, reliable and, preferably, self-powered. To this end, it was proposed that piezoceramic of piezoelectric material be utilized because of their ease of application. These materials were chosen because they can be used both as a actuator and as a sensor. This paper presents a set of numerical investigations performed to highlight the viability of using this material system, and the associated signal analysis that can be employed to detect the presence or the development of disbonds in the adhesive in a bonded repair situation.